An Alternative Model to Overcoming Two Phase Commit Blocking Problem - Sheikh Salah, Hassan Jafar; M. Rimiru, Dr. Richard; W. Kimwele, Dr. Michael (International Journal of Computer (IJC), 2017)
In distributed transactions, the atomicity requirement of the atomic commitment protocol should be preserved. The two phased commit protocol algorithm is widely used to ensure that transactions in distributed environment are atomic. However, a main drawback was attributed to the algorithm, which is a blocking problem. The system will get in stuck when participating sites or the coordinator itself crashes. To address this problem a number of algorithms related to 2PC protocol were proposed such as back up coordinator and a technique whereby the algorithm passes through 3PC during failure. However, both algorithms face limitations such as multiple site and backup coordinator failures. Therefore, we proposed an alternative model to overcoming the blocking problem in combined form. The algorithm was simulated using Britonix transaction manager (BTM) using Eclipse IDE and MYSQL. In this paper, we assessed the performance of the alternative model and found that this algorithm handled site and coordinator failures in distributed transactions using hybridization (combination of two algorithms) with minimal communication messages.